2008
DOI: 10.2749/101686608784218680
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies for Construction of Medium-Rise Buildings in Seismic Regions: The XLAM Case

Abstract: This paper reports on the outcomes of an experimental test performed on a fullscale building constructed using innovative technology. The experimental results are compared with the outcomes of a numerical analysis with the aim to derive the behaviour factor q used in a simplified elastic design of the building under seismic actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 1 publication
(2 reference statements)
3
79
0
2
Order By: Relevance
“…The test configurations were designed based on the typical screw connection details used in the three-storey SOFIE building which was tested in Tsukuba, Japan (Ceccotti 2008). In total twelve screwed CLT connections were investigated in shear and withdrawal directions (Table 1), including parallel (wall-wall and floor-floor) and orthogonal (wall-wall and wall-floor) panel-panel connections.…”
Section: Test Configurations and Experimental Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test configurations were designed based on the typical screw connection details used in the three-storey SOFIE building which was tested in Tsukuba, Japan (Ceccotti 2008). In total twelve screwed CLT connections were investigated in shear and withdrawal directions (Table 1), including parallel (wall-wall and floor-floor) and orthogonal (wall-wall and wall-floor) panel-panel connections.…”
Section: Test Configurations and Experimental Setupsmentioning
confidence: 99%
“…Within this project, racking tests of wall panels with different layouts of connections and openings (Ceccotti et al 2006;Gavric et al 2014a) and pseudo-dynamic tests of a full scale one-storey building were performed (Lauriola and Sandhaas 2006). Next, shaking table tests of a three-storey (Ceccotti 2008) and a seven-storey building were carried out in 2006 and 2007, respectively, the latter one being conducted at the world's largest seismic testing facility (E-Defense) in Miki, Japan. Experimental tests provided excellent outcomes, as the buildings were able to survive a series of strong earthquake ground motions, such as Kobe in 1995, virtually undamaged, while at the same time demonstrating significant energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the seismic performance of CLT structures has been experimentally and numerically studied (e.g., [1]- [7]) and the results confirmed that the cyclic behaviour of metal connections has a key-role in the seismic behaviour of the building. The traditional seismicresistant connections, known as angle brackets and hold-downs, are composed of punched and cold-formed thin steel plates fastened to the panel with nails or screws.…”
Section: Introductionmentioning
confidence: 89%
“…Timber light frame walls sheathed with plywood or OSB, often referred to as 'lightframe construction', are widely used throughout the world (van de Lindt et al 2010;Sartori and Tomasi 2013). Cross laminated walls are extensively used in Europe (Ceccotti 2007;Fragiacomo et al 2011) and, recently, also in North-America (Amini et al 2013;Pei et al 2013) and Japan. This system generally uses a high number of load bearing walls and connections.…”
Section: Introductionmentioning
confidence: 99%
“…This system generally uses a high number of load bearing walls and connections. Shake table tests on cross-laminated timber buildings have shown that they are able to resist multiple earthquakes without being severely damaged (Ceccotti 2007;Hristovski et al 2013). However, recent trends in architectural design call for a reduction in the number of shear walls to allow for open spaces.…”
Section: Introductionmentioning
confidence: 99%